Factors affecting the likelihood of receiving cesarean section among low and high socio-economic group in public health facilities in Mali - Berenice Sorelle W. Gandaho (Chulalongkorn University, 2013)
Thesis (M.Sc.)--Chulalongkorn University, 2012